Graphene Encapsulation for Cells: A Bio-Sensing and Device Platform - Salgado, Shehan (University of Waterloo, 2014)
The generation of new nanoscale fabrication techniques is both novel and necessary for the generation of new devices and new materials. Graphene, a heavily studied and versatile material, provides new avenues to generate these techniques. Graphene’s 2-dimensional form remains both robust and uncommonly manipulable. In this project we show that graphene can be combined with the yeast cell, Saccharomyces cerevisiae, arguably the most studied and utilized organism on the planet, to generate these new techniques and devices. Graphene oxide will be used to encapsulate yeast cells and we report on the development of a method to electrically read the behaviour of these yeast cells. The advantage of an encapsulation process for a cell sensor is the ability to create a system that can electrically show both changes in ion flow into and out of the cell and mechanical changes in the cell surface. Since the graphene sheets are mechanically linked to the surface of the cell, stresses imparted to the sheets by changes in the cell wall or cell size would also be detectable. The development process for the encapsulation will be refined to eradicate excess gold on the yeast cells as well as to minimize the amount of stray, unattached graphene in the samples. The graphene oxide encapsulation process will also be shown to generate a robust substrate for material synthesis. With regards to cell sensing applications, sources of noise will be examined and refinements to the device setup and testing apparatus explored in order to magnify the relevant electrical signal. The spherical topography of an encapsulated yeast cell will be shown to be an advantageous substrate for material growth. Zinc oxide, as a sample material being investigated for its own applications for photovoltaics, will be grown on these substrates. The spherical nature of the encapsulated cell allows for radial material growth and a larger photo-active area resulting in a device with increased efficiency over a planar complement. The zinc oxide nanorods are grown via an electrochemical growth process which also reduces the graphene oxide sheets to electrochemically reduced graphene. XRD analysis confirms that the material synthesized is infact zinc oxide. The nanorods synthesized are 200nm to 400nm in width and 1µm in length. The increase efficiency of the non-planar device and the effectiveness of the encapsulated cell as a growth substrate indicate encapsulated cells as a research avenue with significant potential.
Keywords: Graphene; graphene oxide; Yeast; Zinc Oxide; Solar Cell; Biosensing; Saccharomyces cerevisiae; Chemistry (Nanotechnology)